The Ground and the Sky on the Axis of Metaphor (The metaphorical process of sense-giving to the natural phenomena funded on the orientational metaphors) - ُShayesteh Sadat Mousavi; Mahmoud Rahimi (مطالعات زبانی و بلاغی)
Metaphorical mechanism of mind in sense-giving to the world is the pivot point of this research. The Contemporary Theory of Metaphor which maintains the role of metaphor in sense-giving to the world, is one of the biggest achievements of Cognitive Linguistics. Amongst different kinds of Conceptual Metaphors classified by this theory, Orientational Metaphors involve ways of sense-producing for the world's phenomena via the orientations. As we showed in this research, it might be intangible for a lot of speakers of a certain language how the natural phenomena get connected to spiritual concepts and characteristics – due to their orientational situation-, while there is no essential or natural relation between these concepts and those natural phenomena. By presenting some evidence of the main Persian literary texts, we have shown how the human kind borrows concepts from the theological, spiritual, emotional, physical, and sexual domains and projects them to the domain of natural phenomena. We are also trying to clarify that this projection is funded on the Orienational basis. These evidence declare the process of sense-production for the world through metaphors, and point to the undeniable role of literary texts in stabilization and internalization of conceptual metaphors and handing them over to the next generations.